Software and data technologies 4th International Conference, ICSOFT 2009, Sofia, Bulgaria, July 26-29, 2009 : revised selected papers - ICSOFT (Conference) Sofia, Bulgaria) 2009; Cordeiro, Jose.; Ranchordas, AlpeshKumar; Shishkov, Boris; SpringerLink (Online service). (Heidelberg New York Springer, 2011)
This book constitutes the refereed proceedings of the 4th International Conference on Software and Data Technologies, ICSOFT 2009, held in Sofia, Bulgaria, in July 2009. The 19 revised full papers presented together with two invited papers were carefully reviewed and selected as best papers from 212 submissions. The papers are organized in topical sections on enterprise software technology; software engineering; distributed systems; data management; knowledge-based systems.
Revised conference papers.
Electronic reproduction.
Keywords: Computer software -- Development -- Congresses; Software engineering -- Congresses; Computer programming -- Congresses; Electronic books